2023
DOI: 10.2196/43839
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Usability of an Unguided Web-Based Grief Intervention for Adults Who Lost a Loved One During the COVID-19 Pandemic: Randomized Controlled Trial

Abstract: Background The death of a loved one was a challenge many people faced during the COVID-19 pandemic within the context of extraordinary circumstances and great uncertainty. Grief is an unavoidable part of life, and for most people, feelings of grief decrease naturally over time. However, for some people, grieving can become a particularly painful process with clinical symptoms that may require professional help to resolve. To provide psychological support to people who had lost a loved one during th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…We then tried to confirm and extend these findings using simulations based on real data from a similar previous study conducted by Dominguez-Rodriguez et al (2021 , 2023) . The data included the results of 114 participants, 45 on the treatment condition and 69 on the control condition, which after finishing a waiting period of 36 days, were assigned to the treatment condition.…”
Section: Methods and Analysismentioning
confidence: 81%
See 2 more Smart Citations
“…We then tried to confirm and extend these findings using simulations based on real data from a similar previous study conducted by Dominguez-Rodriguez et al (2021 , 2023) . The data included the results of 114 participants, 45 on the treatment condition and 69 on the control condition, which after finishing a waiting period of 36 days, were assigned to the treatment condition.…”
Section: Methods and Analysismentioning
confidence: 81%
“…The multiple evaluations carried out during the intervention will also provide estimated data on anxiety, depression, stress, sleep quality, experiential avoidance and psychological inflexibility, satisfaction with life, mental psychological well-being, perceived deficits, post-traumatic stress and suicidal ideation, on users in different countries, which can also be compared by the sociodemographic variables collected. Furthermore, although the number of questionnaires implemented in different parts of the study could be perceived as a high number, we ensured to select questionnaires that are short and widely validated, furthermore previous studies conducted by the team members ( Dominguez-Rodriguez et al, 2023 ; Martínez-Arriaga et al, 2023 ) have found that participants do answer all the assessments, and this helps to analyze the impact of the intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early interventions were mainly based on cognitive behavioural therapy (CBT) (Kersting et al, 2011 ; Kersting et al, 2013 ; Lange et al, 2000 ; Litz et al, 2014 ; van der Houwen et al, 2010 ; Wagner et al, 2006 ), including self-confrontation/exposure, cognitive restructuring/cognitive reappraisal, and social sharing as elements. Recently, some interventions were innovatively designed to combine CBT with grief theory such as the dual process model of coping with bereavement (DPM) (Brodbeck et al, 2019 ) and the Worden’s task model of grieving (Dominguez-Rodriguez et al, 2023 ). Internet-based grief interventions have been also expanded to art therapy based on solution-focused brief therapy and the meaning-making approach to bereavement (Park & Cha, 2023 ) and yoga intervention combining physical exercise and mindfulness cultivation (Huberty et al, 2020 ; Sullivan et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analyses of RCT demonstrated that Internet-based grief interventions are effective, with moderate to large effect sizes (Wagner et al, 2020 ; Zuelke et al, 2021 ). While studies included in the meta-analyses mostly adopted therapist-assisted interventions, Internet-based self-help grief interventions were also effective enough to improve mental health (Dominguez-Rodriguez et al, 2023 ; Huberty et al, 2020 ; Reitsma et al, 2023 ; Schrauwen, 2021 ; van der Houwen et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%